Analisis Perlindungan Hukum dalam Pencegahan dan Penanganan Kekerasan Seksual di Lingkungan Perguruan Tinggi - Bustaman, Bustaman; Machmud, Amir (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Sexual violence in higher education institutions is a serious issue that requires effective legal protection. Despite various regulations being issued to address sexual violence, their implementation in universities still faces many challenges. This study aims to analyze the legal protection in the prevention and handling of sexual violence in higher education institutions and to identify the factors affecting its effectiveness. A qualitative research approach with a case study design was used, involving in-depth interviews and document analysis related to existing regulations in several universities. The findings show that, although comprehensive regulations such as Law No. 12 of 2022 on Sexual Violence Crimes and Ministerial Regulation No. 30 of 2021 have been established, their implementation is hindered by the low legal awareness among academic communities, limited resources within the Sexual Violence Prevention and Handling Task Force (Satgas PPKS), and the strong patriarchal culture within campuses. To enhance the effectiveness of legal protection, it is necessary to strengthen the capacity of Satgas, intensify socialization efforts, and foster a campus culture that is more supportive of victims. This study concludes that optimal legal protection requires collaboration between the government, higher education institutions, and the campus community to create an environment free from sexual violence.